Safety and efficacy of Actisaf® Sc47 (Saccharomyces cerevisiae CNCM I‐4407) as a feed additive for cattle for fattening, dairy cows, weaned piglets and sows. (7th March 2019) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Actisaf ® Sc47 for dairy cows, cattle for fattening, weaned piglets and sows when used as a zootechnical additive. Actisaf ® Sc47 consists of viable cells of a strain Saccharomyces cerevisiae and is marketed in three formulations. The FEEDAP Panel considers that the three available formulations are equivalent when used to deliver the same dose of the microorganism in feed. The active agent fulfils the requirements of the qualified presumption of safety approach to the assessment of safety. Since the additive is composed of the active agent only, Actisaf ® Sc47 is also presumed safe for the target animals, consumers of products derived from treated animals and the environment. Actisaf ® Sc47 is not a skin irritant. In the absence of data, no conclusions can be drawn on the eye irritancy and dermal sensitisation potential of the additive. Inhalation exposure is unlikely. The additive has the potential to be efficacious in weaned piglets and sows to have benefits in piglets at the recommended dose of 5 × 10 9  CFU/kg feed. Insufficient evidence was provided to conclude on the efficacy of the additive in dairy cows and cattle for fattening.